Foundations for local governance : decentralization in comparative perspectives - Saitō, Fumihiko, 1961- (Physica Springer, 2008)
Various forms of decentralization are recently pursued in the world, including developing countries. However, there has not been a coherent framework to access these intended outcomes generated by decentralization measures implemented in Asian and African countries. This book provides such a framework based on comparative analyses of different experiences of decentralization measures in six developing countries, where the policy rationale to???bring services closer to people??? originated in different socio-political backgrounds. Although decentralization measures are potentially useful for a.